Gender-Based Preferences and Experiences in Using Interactive Quiz Platforms: A Qualitative Study of EFL Students - Hasibuan, Sri Wahyuni; Zulfikar, Zulfikar; Nasution, Dina Syarifah (Tamaddun Life, 2025)
This study investigates gender-based differences in students’ preferences and experiences with interactive quiz platforms Quizizz and Kahoot among English Tadris students at STAIN Mandailing Natal. Employing a qualitative descriptive approach, the research involved 30 participants, equally divided by gender (15 male and 15 female students), selected through purposive sampling. Data were collected through semi-structured interviews and document analysis, then analyzed thematically using Braun and Clarke’s framework. Four primary themes guided the analysis: ease of use, technical and accessibility features, learning motivation, and material comprehension. Findings indicate that while both male and female students preferred Quizizz for its intuitive design and support for self-paced learning, notable gender differences emerged in motivation and usage patterns. Male students favored Kahoot due to its competitive features, such as real-time leaderboards and time-bound questions, which enhanced engagement and fostered a stimulating classroom environment. Conversely, female students valued Quizizz’s calm, flexible learning experience, which minimized anxiety and allowed for deeper understanding through repeated practice and instant feedback. The results suggest that gender plays a critical role in shaping students’ engagement with educational technologies, particularly those that integrate gamification elements. The study highlights the importance of aligning technological tools with learners’ individual preferences to optimize engagement and learning outcomes. Practical implications point to the need for more inclusive and adaptive instructional strategies when integrating digital platforms in EFL settings. Future research is recommended to explore larger samples and diverse educational contexts for broader generalizability.